Microwave assisted polymeric modification of graphite oxide and graphite by poly(allyl diazoacetate-co-acrolein). (5th December 2019) - Li, Yan; Tang, Jian; Liu, Yun; Li, Tao; Ma, Dongxu; Gao, Jie; Yang, Jie; Zhou, Yue; Zhang, Yue-Fei
Abstract: A novel method of polymeric modification of graphite oxide and graphite under microwave irradiation is reported in this article. The tetrapolymer of poly(ADA- co -Ac) is firstly synthesized via allyl diazoacetate (ADA) and acrolein (Ac) with diazo group in the side chain. The diazo group of poly(ADA- co -Ac) can react with CC bond of graphite oxide/graphite covalently, which is supported by FT-IR, CRM, XPS, XRD and TGA. SEM and TEM images show that the grafted copolymers distribute homogeneously on the surface of the functionalized composites. AFM images exhibit that the thickness of nanosheets is consistent with multilayer graphene sheets, which indicates that the graphene sheets can be exfoliated from graphite oxide/graphite after functionalization. This method provides a novel way to functionalize graphene and can even fabricate polymeric graphene sheets from graphite directly, which may have potential applications in the field of graphene-based materials. Graphical abstract: Unlabelled Image Highlights: A novel method to fabricate graphene/polymer composites assisted by microwave was provided. The covalent functionalization occurred between diazo group from the polymer and C=C in graphite. Graphene sheets could be exfoliated from graphite oxide/graphite after functionalization. The solubility of graphene/polymer composites in organic solvents was obviously improved.